2019
DOI: 10.31557/apjcp.2019.20.4.1223
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Circulating MiR-21 Expression as a Potential Biomarker for Therapeutic Monitoring and Clinical Outcome in Breast Cancer

Abstract: Background: Aberrant patterns of microRNA expression have been highlighted as a potential clinical biomarker in breast cancer as the most frequent cancer among women that contributes nearly a quarter of total cancer incidence in 2018. Upregulation of microRNA-21 (miR-21) is associated with adverse clinical outcomes in breast cancer. However, the use of circulating free miR-21 as a non-invasive biomarker for diagnosis and therapeutic monitoring in breast cancer is not well established. We quantified the levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 41 publications
1
23
1
Order By: Relevance
“…Although expression of miR-155 in primary breast cancer tissue has been associated with the prognosis, limited study has reported the correlation of circulating miR-155 with clinical outcomes (Jang et al, 2017;Lü et al, 2017). In contrast to our previous study using circulating miR-21 (Anwar et al, 2019b), our current study showed that upregulation of circulating miR-155 was associated with better PFS. Although miR-155 is commonly associated as oncomir, our study showed the upregulation with better PFS.…”
Section: Discussioncontrasting
confidence: 99%
“…Although expression of miR-155 in primary breast cancer tissue has been associated with the prognosis, limited study has reported the correlation of circulating miR-155 with clinical outcomes (Jang et al, 2017;Lü et al, 2017). In contrast to our previous study using circulating miR-21 (Anwar et al, 2019b), our current study showed that upregulation of circulating miR-155 was associated with better PFS. Although miR-155 is commonly associated as oncomir, our study showed the upregulation with better PFS.…”
Section: Discussioncontrasting
confidence: 99%
“…This study aims at evaluating the diagnostic and predictive role of the expression of some candidate miRs, including miR-10b, miR-21, miR-155, miR-181a, miR-145, and let-7a, in LABC. In agreement with previous findings, 40,4552 we demonstrated that the expression of the oncomiR-10b, oncomiR-21, and oncomiR-181a was significantly increased in LABC patients, whereas tumor suppressor miR-145 and let-7a expressions were significantly down-regulated, compared to healthy subjects. Similarly, the dysregulation of serum miR-10b, miR-21, miR-125b, miR-145, miR-155, miR-191, and miR-382 in breast cancer patients has been reported by Mar-Aguilar et al, 53 who concluded that these seven miRs can be used as a biomarker in breast cancer.…”
Section: Discussionsupporting
confidence: 93%
“…Among onco-miRs, miR-21 is widely recognized as the onco-miR in any cancer types per se. Several clinical reports revealed that the upregulation of miR-21 expression in cancer tissue and blood was positively related with chemoresistance, poor progression-free survival, worse overall survival in breast [ 54 ], pancreas [ 55 ], rectal [ 56 ], squamous cancer [ 57 ], colorectal [ 58 ], lung [ 59 ], renal cancers [ 60 ] and lymphoma [ 61 ]. miR-125 was also reported as an onco-miR among the cancer patients with squamous cancer carcinoma [ 62 ], gastrointestinal stromal tumor [ 63 ], oesophagus cancers [ 64 ], whereas it was recognised as an anti-onco-miR among cervical [ 65 ], gallbladder [ 66 ] and colorectal cancers [ 67 ].…”
Section: Main Bodymentioning
confidence: 99%